Respuesta :

Im going to assume you know the formula.
sooo.
x= -11 +- √ (11)² -4 (1) (-15)
     --------------------------------- 
          2(1)

= -11 +- √121- (-60)
  -------------------------
              2

= -11 +- √181
   -----------------
            2

= -11 +- 13.45
   -----------------
             2

Either:                                                Or:
                                                          X = -11 - 13.45
  x = -11 + 13.45                                       ---------------
                                                                        2
       ----- ----------                               
              2       
   x = 1.23                                           x= -12.23
ACCESS MORE